Successful Rehabilitation of Partial Edentulous Maxilla and Mandible with New Type of Implants: Molecular Precision Implants - Matteo Danza; Dorina Lauritano; Francesco Carinci (Case Reports in Medicine)
The extraction of teeth results in rapid bone resorption both vertically and horizontally in the first month. The loss of alveolar ridge reduces the chance of implant rehabilitation. Atraumatic extraction, implant placement in extraction socket, and an immediate prosthesis have been proposed as alternative therapies to maintain the volume and contours tissue and reduce time and cost of treatment. The immediate load of implants is a universally practiced procedure; nevertheless a successful procedure requires expertise in both the clinical and the reconstructive stages using a solid implant system. Excellent primary stability and high bone-implant contact are only minimal requirements for any type of implant procedure. In this paper we present a case report using a new type of implants. The new type of implants, due to its sophisticated control system of production, provides to the implantologist a safe and reliable implant, with a macromorphology designed to ensure a close contact with the surrounding bone.